COSMO-RS and DFT studies on development and optimization of quercetin as a chemosensor for Fe3þ recognition in aqueous medium - Abdullah, Erna Normaya; Mad Saad, Muhammad Fazli; Ahmad, Mohammad Norazmi; Ku Bulat, Ku Halim (Elsevier B.V., 2019)
Quercetin is known as a bioflavonoid compound that has been successfully optimized to be a chemo- sensor probe for Fe3þ recognition. The sensitivity of quercetin towards Fe3þ increased in DMSO:deionized water with a 9:1 ratio at pH 4. There was also no significant interference from other metal ions, such as Kþ, Cr3þ, Agþ, Cd2þ, Mg2þ, Pb2þ, Co2þ, Ni2þ, Zn2þ and Cu2þ in the selectivity optimization. The detection limit of the probe was 20.5 mM. The stoichiometry of 1:1 quercetin:Fe3þ was calculated using the Job plot method. The sigma profile was calculated using COSMO-RS, which showed that quercetin formed stronger hydrogen bonds with the DMSO solvent. Density functional theory (DFT) calculations, such as molecular electrostatic potential (MEP) and the Fukui function, were performed to visualize and clarify the region of interaction between quercetin and Fe3þ. The TD-DFT method was successfully used to investigate the electronic properties of quercetin and quercetineFe3þ and it showed good agreement between experimental and theoretical results.